The Abuse of Power Philosophy in Government Administration - Asmuni Asmuni (Media of Law and Sharia, 2024)
Government authority and governance in Indonesia are governed by Law No. 30 of 2014, which is titled "Government Administration." Following the implementation of this law, however, a problem arose regarding the government's abuse of authority. The objective of this study is to examine specific instances in which the government has improperly exercised its authority subsequent to the implementation of Law No. 30 of 2014. This investigation employs a normative methodology. This study examines established legal norms or regulations in order to comprehend and evaluate a legal phenomenon. As evidenced by the research findings, instances of governmental authority abuse abound, encompassing the implementation of detrimental policies, human rights violations, and the manipulation of data to advance political objectives. This abuse of authority is exacerbated by transparent practices, inadequate government accountability, and ineffective oversight mechanisms.